Signifikansi Konsep Istibdal Dalam Sistem Pengurusan Wakaf: Analisis Dari Perspektif Fiqh Dan Undang-undang - Hisham Sabri; Siti Mashitoh Mahamood (Universiti Sains Islam Malaysia, 2024)
Waqf, as one of the ijtima’ie sector is an important agent for Muslim economic development. However, the abandoned assets of waqf need to be strengthened in order to continue the benefits of the waqf. This study aims to analyze the significance of istibdal concept in waqf management. Content analysis method is applied to discuss the conditions of istibdal implementation from various mazhab and law practitioners to resolve issues arising from the wakaf assets. This study found that istibdal method could be a potencial mechanism to empower waqf asset value within the approval and jurisdiction from state fatwa committee. Comprehensive analysis of administration and laws issues may discussed by sampling methods towards istibdal implementation at related states. It is hoped that the finding on istibdal waqf study will be usefull for the State Islamic Religious Council to enhance waqf management system.